Associations between urinary phthalate concentrations and antral follicle count among women undergoing in vitro fertilization - Yao, Yangcheng; Du, Yaoyao; Guo, Na; Liu, Fenghua; Deng, Taoran; Li, Yufeng (Frontiers in Endocrinology, 2024)
BackgroundPhthalates are ubiquitously used in a variety of products and have an adverse effect on folliculogenesis. However, previous epidemiological studies on the associations between phthalate exposure and antral follicle count (AFC) produced conflicting results. The present study aimed to evaluate the associations between urinary phthalate metabolite concentrations and AFC among women undergoing in vitro fertilization (IVF).MethodsWe collected 525 urine samples and measured 8 phthalate metabolites from IVF patients. Poisson regression models were conducted to evaluate the associations between phthalate metabolite concentrations and AFC. In addition, participants were stratified into a younger group (< 35 years) and an older group (≥ 35 years) to explore the potential effect modification by age. We also performed sensitivity analyses by restricting our analyses to only infertile women diagnosed with tubal factor infertility to test the robustness of the results.ResultsSignificant positive associations were observed among urinary MBP, MEOHP and ∑PAEs concentrations and AFC after adjusting for age, BMI, year of study and infertility diagnosis. Compared with women in the first tertile, women in the third tertile of MBP and MEOHP had 7.02% (95% CI: 1.18%, 12.9%) and 8.84% (95% CI: 2.83%, 14.9%) higher AFC, respectively, and women in the second and third tertiles of ∑PAEs had 6.19% (95% CI: 0.37%, 12.0%) and 9.09% (95% CI: 3.22%, 15.0%) higher AFC, respectively. In addition, MBP, MEOHP and ∑PAEs also had significant positive associations with AFC in trend tests for dose-response. In the age-stratified analysis, we found a stronger relationship between phthalate metabolite concentrations and AFC among older women and an inverse association among younger women. We observed similar results in the sensitivity analyses.ConclusionWe found positive associations between phthalate exposure and AFC, which support the idea that phthalate exposure may accelerate primordial follicle recruitment and lead to higher AFC in women undergoing IVF. More studies are needed to better understand their relationships.